DEIXIS ANALYSIS OF JALALUDDIN RUMI'S LOVE STATEMENT POEM - Rofiatun Hasanah; Ahmad Mahfudillah Syam (STAI Nusantara Kota Banda Aceh, 2026)
This study examines the use and function of deictics in the poem “Perjalanan Cinta” by Jalaluddin Rumi, a renowned Sufi poet. Deictics is a phenomenon related to the understanding of conversational context, encompassing personal, spatial, and temporal aspects. Using a descriptive qualitative approach and sociopragmatic deictic theory, this research explores how deictic elements shape profound spiritual meaning and the mystical relationship between the servant (I) and the Creator (You). The analysis reveals a dominance of personal deictics, particularly the first- and second-person singular perspectives, reflecting an intimate dialogue within the spiritual journey (tariqah). Deictics of place and time function as symbols of transcendental space and eternal time, not merely as physical markers. In conclusion, deictics in Rumi’s poetry function not only as connecting elements within the text but also as poetic-philosophical tools that link worldly reality with sacred divine love.